Biometrics and Neuroscience Research in Business and Management : Advances and Applications - Alcañiz, Mariano; Appel, Uriel; Araujo, Arthur; Berg, Pekka; Bigne, Enrique; Brendl, Miguel; Cardoso, Lucilia; Cerf, Moran; Cerf, Moran; Chicchi Giglioli, Irene Alice; Dias, Francisco; García, Aitana; et al. (De Gruyter, 2024)
This book is designed to impart and convey knowledge as well as understanding of the range of biometric technologies and cybertechnologies, while also stressing their advantages and disadvantages. The authors develop an appreciation for and breadth of knowledge that spans the full range of neuroscience sub-disciplines, including behavioural, cognitive, and computational neuroscience. Furthermore, the content of the book is geared to be able to place neuroscience into an ethical context, especially showing how studying the brain and behaviour can contribute to the resolution of ethical, social, and environmental issues.